Kisspeptin-10 treatment generated specific GnRH expression in cells differentiated from rhesus monkey derived Lyon NSCs. (4th May 2017) - Huma, Tanzeel; Hu, Xintian; Ma, Yuanye; Willden, Andrew; Rizak, Joshua; Shahab, Muhammad; Wang, Zhengbo
Graphical abstract: Highlights: Neural stem cell therapies are dependent on accurate control of cell differentiation. Kisspeptin involved in reproductive neuroendocrine homeostasis. KP-10 signaling-induced NSCs differentiate into GnRH neuron-like cells in vitro. NSC therapies for GnRH deficiency reproductive disorders like IHH may be possible. Abstract: Embryonic stem cells (ESCs) have enormous potential as novel cell-based therapies, but their effectiveness depends on stem cell differentiation and specific signaling regulators, which remain poorly understood. In this study, a kisspeptin peptide (KP-10) was used at different dosages to determine whether rhesus macaque-derived tau GFP-Lyon ES cells underwent kisspeptin-specific neuronal differentiation. It was found that KP-10 exhibited an anti-proliferative effect on the cells and led to morphological changes and cellular differentiation consistent with neuronal stem cell (NSC) development. The cells differentiated into Gonadotrophin Releasing Hormone (GnRH) neuronal-like cell types in response to the KP-10 treatment. There has been a previously observed connection between kisspeptin signaling, GnRH neurons and their dysfunction found in congenital disorders like idiopathic hypogonadotropic hypogonadism (IHH). Although therapeutics are a still a far-off goal, the formation and development of GnRH-positive neuronal-like cells following the application of KP-10 to Lyon NSC cells opens the door for future NSC-based therapies to treat specific reproductive disorders.